Credibilidade jornalística no Regime de informação mediado pelo algoritmo - Magalhães, Daniel Lima (2021)
We start this research from the hypothesis that the algorithmization of the informational mediation regime has altered the construction process of journalistic credibility. Our goal is to contribute to the ongoing practical-epistemological debate on the determinants of this specific credibility vis-à vis the public, professionals, and mediation itself, hereby represented in the ascendancy of sociotechnical networks and algorithmic technologies of communication and information. To do so, we divided this work into three parts: in the first, we carried out a theoretical framework on the concept of journalistic credibility based on the dialectic of credibility proposed by Lisboa and Benetti (2017) and the journalistic deontology studied by Carlos Camponez (2009); in the second, we examine the algorithmic mediation and its importance for the establishment of a new global hegemony in the information regime, phenomena we describe from the studies of González de Gómez (2012) and Bezerra (2017a, et al 2017b) and the theories of Bruno Latour (1994) and Bernd Frohmann (1995); and, in the third, we analyze the effects of this regime on journalistic authority and public confidence through the events of automation in journalistic routine originating what researchers have called computational journalism (ANDERSON, 2012), automated journalism (CARLSON, 2014), robotic journalism (SCHULTZ and SHEFFER, 2017) or algorithmic journalism (DIAKOPOULOS, 2014), the latter adopted by us. Thus, we discuss the centrality of algorithms for the contemporary information society and conclude with some perspectives for the future of journalism, its reorganization and renewal within this ecosystem, as well as strategies to guarantee the necessary stability for the construction and maintenance of credibility.